Habit Watching Movie With English Subtitles as an Alternative in Improving on Students' Reading Skill - Nadivah Nadivah; Suryadi Suryadi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The objective of this study is to establish a correlation between the practice of watching English language films and the utilization of English subtitles as a substitute method to enhance students' English reading comprehension. The research was carried out at SMA Negeri 1 Tirtayasa. This study seeks to ascertain the extent to which students' comprehension improves by regularly watching English films with subtitles. The employed methodology is quantitative, focusing on a population of students in classes XII Science 1, 2, 3, and 4. Subsequently, a total of 76 students were included in the sample. The collected data pertains to the English reading comprehension test of the students. The independent variable in this study refers to the practice of watching English films with English subtitles, whereas the dependent variable pertains to the English reading comprehension skills of the students. The investigation yielded substantial data. The term "2-tailed" refers to a statistical test that considers both directions of an effect or relationship.The data acquired from the control class was 77.29, whereas the data from the experimental class was 79.63. Consequently, the treatment has had a notable impact on the kids' reading comprehension, resulting in a commendable level of proficiency. The employed methodology is highly effective in enhancing the students' English reading comprehension.